The everyday life of Hindu nationalism : an ethnographic account - Mathur, Shubh (Three Essays Collective, 2008)
Shubh Mathur s account of the resistible rise of Hindu chauvinism in the north Indian state of Rajasthan is at once a remarkable piece of contemporary scholarship and a great human document. This is a searingly honest piece of writing, with an unashamedly partisan position, but without compromising the demands of theoretical rigor and empirical depth. Shubh Mathur s book provides a fine-grained account of the tortured response of India s Muslims to the emerging shifts in a social order that has begun to view them with increasing weariness, impatience and a hectoring command to assimilate . Raza Mir It is an error to read fascism as an abnormality; one should, in fact, seek the links between fascism and normality . Shubh Mathur s work brilliantly shows how the cultural logic and institutional power of Hindutva have become deeply entrenched in everyday life itself . Sadanand Menon This is an ethnographic account of the rise of Hindu nationalism in the north Indian state of Rajasthan during the period 1990-94. It looks at the transformation of cultural meanings in everyday life that make possible the political success and the anti-minority violence of the Hindu right. Media and academic accounts of the Hindu right that present images of religious frenzy and fanaticism are misleading because they draw attention away from the world of the everyday and the ordinary, from the homes, workplaces, schools and communities where the realities of Hindu nationalism are created and maintained. This book takes seriously the claims of RSS activists that theirs is a cultural organization, and that its main task is character- building , in order to answer the central question: How does one comprehend the selves that are capable of the extraordinary violence witnessed in India at the turn of the millennium? The patterns of anti-minority violence that accompanies the rise of Hindu nationalism show that it follows not a political or economic logic, but a cultural one. The geographic and demographic distribution of violence maps and confirms cultural beliefs about the nation and its enemies. Finally, this book argues that media and academic discourses on Hindu nationalism function to produce what has been called cultural anesthesia , diffusing and deflecting questions about agency and accountability while silencing the experience of the victims and excluding the cultural idioms which provide them means of comprehension and healing.